REGIONAL GENDER DISPARITIES IN INDONESIA: A COMPARATIVE - Luthfia, Deba; Handoko, Michelle; Sianipar, Rouli Chessa Joellen; Putri, Dyah Ayu Ariska (Bina Ekonomi, 2025)
Indonesia’s socio-economic landscape is a tapestry woven from historical legacies, cultural norms, and dynamic economic forces. At the heart of this mosaic lies Java, the most populous and economically advanced island, often serving as a developmental benchmark. However, prosperity does not flow uniformly across the archipelago. Sumatra, Bali, Sulawesi, and Kalimantan—each with its unique context-grapple with gender-related challenges that shape the lives of their inhabitants. By dissecting these regional disparities, we uncover the intricate interplay of factors influencing gender outcomes. Our investigation relies on data extracted from the 2023 Sakernas survey. We hone in on critical indicators of gender disparities: work hours, income discrepancies, educational access, and social safety nets. Employing a descriptive and typological lens, we juxtapose these indicators across the five islands. This method allows us to discern patterns, outliers, and distinctive features specific to each region. Our research serves a dual purpose: it enriches academic discourse and informs policy formulation. By spotlighting the variations in gender inequities, we pave the way for targeted interventions. Policymakers can leverage these insights to tailor programs that address the unique hurdles faced by women and men in different locales. Moreover, our findings contribute brushstrokes to a more nuanced portrait of Indonesia’s socio-economic fabric-one that transcends mere statistical aggregates and delves into the intricate brushwork of gender dynamics.